Comparison of 18F-FDG and 68-PSMA-11 in PET for prostate cancer diagnosis - Natalia Fulle; Gaianê Sabundjian (Brazilian Journal of Radiation Sciences)
Prostate cancer is the second most incident neoplasm in men, except for non-melanoma skin cancer, and has the second highest mortality rate in Brazil. Early diagnosis increases the chances of cure and enables a less aggressive treatment for the patient. Nuclear Medicine presents effective alternatives for prostate cancer diagnosis, such as Positron Emission Tomography (PET) or PET and Computed Tomography (PET/CT) imaging.  The aim of this study is to compare the advantages and disadvantages of the radiopharmaceuticals 18F-FDG and 68Ga-PSMA-11 used for PET or PET/CT in the diagnosis of this type of cancer. Compared to 18F-FDG, 68Ga-PSMA-11 has some advantages such as its availability by means of generators, the independent production of a cyclotron facility and its theranostic potential. The disadvantages compared to 18F-FDG are the scalability of 18F-FDG production compared to limited generator production.  Despite its favorable characteristics, the radiopharmaceutical 18F-FDG has limitations in the diagnosis of some types of tumors, such as prostate cancer. All the favorable and unfavorable aspects of these two radiopharmaceuticals are presented in this work.